Social structure and regional development : a social geography perspective : essays in honour of Professor Moonis Raza - Ahmad, Aijazuddin; Raza, Moonis (Rawat Publications, 1993)
Festschrift honoring Professor Moonis Raza, Indian geographer, educational planner and administrator.